2017
DOI: 10.5902/1980509826451
|View full text |Cite
|
Sign up to set email alerts
|

Dinâmica De Populações De Espécies Arbóreas Em Um Fragmento De Floresta Ombrófila Mista Montana Em Lages, Santa Catarina

Abstract: O presente estudo teve como principal objetivo avaliar a dinâmica de populações de espécies arbóreas, em um fragmento de Floresta Ombrófila Mista Montana, no Município de Lages, Santa Catarina - SC, ao longo de um período de quatro anos (2008-2012). Para isto, em todas as espécies amostradas em 50 parcelas permanentes de 10 x 20 m, foram determinadas as guildas de regeneração [Pioneiras (P), Climácicas Exigentes em Luz (CEL) e Climácicas Tolerantes ao Sombreamento (CTS)] e as taxas de dinâmica (mortalidade, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
(9 reference statements)
0
4
0
1
Order By: Relevance
“…In the Atlantic Forest of Brazil, differences in historical disturbances resulted in fragments of secondary forests that are in different stages of recovery but have a large proportion of their biodiversity conserved (Cruz et al, ; Ribeiro, Metzger, Martensen, Ponzoni, & Hirota, ; Salami et al, ). Under this scenario, to improve conservation and management actions for these forest remnants, we conducted a long‐term study in secondary forests in the southern region of the Atlantic Forest to investigate how these forests changed in time and space in relation to structure (abundance and basal area), floristic richness, species composition, demographic dynamics rates, alpha diversity and spatial beta diversity.…”
Section: Introductionmentioning
confidence: 99%
“…In the Atlantic Forest of Brazil, differences in historical disturbances resulted in fragments of secondary forests that are in different stages of recovery but have a large proportion of their biodiversity conserved (Cruz et al, ; Ribeiro, Metzger, Martensen, Ponzoni, & Hirota, ; Salami et al, ). Under this scenario, to improve conservation and management actions for these forest remnants, we conducted a long‐term study in secondary forests in the southern region of the Atlantic Forest to investigate how these forests changed in time and space in relation to structure (abundance and basal area), floristic richness, species composition, demographic dynamics rates, alpha diversity and spatial beta diversity.…”
Section: Introductionmentioning
confidence: 99%
“…According to Dallabrida et al (2019), the dynamics of the bush-tree component is not a spatially homogeneous process, having factors ecological, biotic, and abiotic influencing the demographic rates of the regenerative component and which will affect biodiversity conservation (Salami et al, 2014, Arroyo-Rodriguez et al, 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals of A. angustifolia were not present in greater numbers than other species; however, they constituted the largest diameters. Araucaria angustifolia was also shown to be dominant in Mixed Ombrophilous Forests in studies by Figueiredo-Filho et al (2010), Higuchi et al (2013), Sawczuk et al (2014), Cubas et al (2016), andSalami et al (2017).…”
Section: Horizontal Structural Dynamicsmentioning
confidence: 94%
“…A study by Figueiredo-Filho et al (2010), which evaluated the dynamics of a Mixed Ombrophilous Forest, found that there was an increase in the basal area when average entry rate was close to 3% year -1 and mortality rate was between 1 and 2% year -1 . According to Salami et al (2017), variations in dynamics rates among different areas on a regional scale reflect differences in successional stages, environmental variables, and disturbance history.…”
Section: Tree Layer Dynamicsmentioning
confidence: 99%